Oficinas como dispositivo na formação de professores: produção discursiva sobre sexualidade - Tadielo, Francine Netto Martins (2013)
This research had as challenge to think on how power and knowledge operations function, in the teachers and future teachers discourses, considering questions involving sexuality. The desire to think in this way is related to anxieties that seek reflecting on roles attributed to the teachers, such as, to make working, at school, knowledge considered necessary, through devices as public politics, in special, the ones that point out the treatment of sexuality questions, in the classroom, by the teacher. For that, it was carried out workshops with eleven future teachers of Biology Course from UFSM and eighteen teachers of a state school from Santa Maria/RS. The workshops were lead through the space opening to conversation, to talk about, to receive and bring troubles, from the diversification of particular and collective knowledge. The materials, employed in this context, were: a) the movie O Beijo no Asfalto (1981), based on Nelson Rodrigues work, which shows the transformation in a man life after a kiss; b) fragments of the work Mulheres que amam demais , by Robin Noowod (1995), which presents women troubles and their loving relationships; c) the kit escola sem homofobia , part of Federal Government actions, in order to give space to sexuality questions at school; as weel, d) articles, from internet, that bring the repercussion of the Kit at school context. With the teachers group from school, besides working with these materials, we talked about the short film Não gosto de meninos (2011), directed by André Matarazzo and Gustavo Ferri, which presents people report on how people deal with homosexuality as in family context as in social one. From the participants discourses, it was possible to perceived that the search for ready solutions about how to dealt with sexuality or the search for more appropriate ways to talk on sexuality can be reflected from what Foucault (1999a) presents about this subject, it means, that sexuality is a historical device, that penetrates in the bodies in a detailed way, controlling the people in a perspective each more global. The device, in this sense, is pointed out as a set of power and knowledge strategies, which establish connections to precise discourses, produce truths and these truths effects. In this way, how we had built the way of being in the world can be understood as effects from these connections of power and knowledge that act on our bodies and lead us to a model of teacher, of student, of relationships, etc. The written of this research allows to show how the process of this work caused surprises, challenges and transformations from the change of points of view and from the meaning construction in collective during the workshops.